Duration of peripheral intravenous catheter use and development of phlebitis - Rita Andriyani; Hindra Irawan Satari; Pustika Amalia (Paediatrica Indonesiana, 2013)
Background Phlebitis is a common complication in patients withperipheral intravenous catheters, in addition to extravasation andbacterial colonization. Phlebitis may increase morbidity and lengthof hospitalization. One factor contributing to the rate of phlebitis isthe duration of peripheral intravenous catheter use. Several adultstudies have shown that the risk of developing phlebitis increasedwhen the peripheral intravenous catheter was used for more than72 hours. However, in pediatric patients this risk has not beenconsistently observed. As such, there is no recommendation forroutine catheter removal every 72 hours in children.Objective To assess for a possible relationship between durationof peripheral intravenous catheter use and the development ofphlebitis.Methods This analytic observational study had a case controldesign. Subjects consisted of 73 case subjects and 73 controlsubjects. We collected subj ects' data through history-taking andclinical examinations. The duration of peripheral intravenouscatheter use was reported in hours.Results From October 2011 to February 2012, 146 children fromthe Department of Child Health at Dr. Cipto MangunkusumoHosp ital and Tangerang Hospital who used peripheral intravenouscatheters were enrolled in this study. There was no significantdifference between <7 2-hour and 2: 72-hour duration ofperipheral catheter use (OR 1.31; 95%CI 0.687 to 2.526;P= 0.407) on the development of phlebitis.Conclusion We observe no relationship between duration ofperipheral intravenous catheter use and the development ofphlebitis in our subjects.